2021
DOI: 10.1088/1361-6528/abe3b4
|View full text |Cite
|
Sign up to set email alerts
|

DNA-templated silver nanoclusters as an efficient catalyst for reduction of nitrobenzene derivatives: a systematic study

Abstract: Nitrobenzene compounds are highly toxic pollutants with good stability, and they have a major negative impact on both human health and the ecological environment. Herein, it was found for the first time that fluorescent DNA-silver nanoclusters (DNA-AgNCs) can catalyze the reduction of toxic and harmful nitro compounds into less toxic amino compounds with excellent tolerance to high temperature and organic solvents. In this study, the reduction of p-nitrophenol (4-NP) as a model was systematically investigated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Enzymes are widely applied in medicine, agriculture, and food processing; however, the catalytic activities of enzymes are usually lost after exposure to harsh conditions. Currently, huge efforts have been devoted to the investigation of efficient artificial enzymes (nanozymes), which possess enzymelike activities and stability in harsh environments . For example, several nanoparticles have been found to exhibit enzyme-like activity, such as Au NPs and MnO 2 that possess oxidase-like activity, as well as Fe 3 O 4 and TiO 2 that possess mimetic horseradish peroxidase (HRP) activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes are widely applied in medicine, agriculture, and food processing; however, the catalytic activities of enzymes are usually lost after exposure to harsh conditions. Currently, huge efforts have been devoted to the investigation of efficient artificial enzymes (nanozymes), which possess enzymelike activities and stability in harsh environments . For example, several nanoparticles have been found to exhibit enzyme-like activity, such as Au NPs and MnO 2 that possess oxidase-like activity, as well as Fe 3 O 4 and TiO 2 that possess mimetic horseradish peroxidase (HRP) activity.…”
Section: Introductionmentioning
confidence: 99%
“…17−20 Currently, huge efforts have been devoted to the investigation of efficient artificial enzymes (nanozymes), which possess enzymelike activities and stability in harsh environments. 21 For example, several nanoparticles have been found to exhibit enzyme-like activity, such as Au NPs 22 and MnO 2 23 that possess oxidase-like activity, as well as Fe 3 O 4 24 and TiO 2 25 that possess mimetic horseradish peroxidase (HRP) activity. Although great development has been achieved, the types of reaction that can be catalyzed by enzymes are still limited; thus, to realize practical applications, it is essential to make the nanozyme particles realize extended applications in the enzyme/nanozyme cascade.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These results indicate that nucleosides or DNA provide more possibilities for regulating the enzymatic activity of MNPs. Reaction conditions were sys-tematically optimized to further expand the application of DNA-Ag NCs as nanocatalysts with 4-nitrophenol (4-NP) reduction as a model reaction and revealed their potential for boosting degradation of a series of nitrobenzene derivatives in industry [122]. It was found that DNA-Ag NCs maintained their catalytic activity even at the high temperature of close to 100 °C, which drastically expanded their application scope.…”
Section: Biocompatibility Of Antibacterial Dna-mncsmentioning
confidence: 99%
“…Nitrobenzene derivative has also been linked to carcinogenesis, mutagenesis, skin sensitization, and hepatotoxicity (9). Therefore, the useful understanding of this material on the mechanism and action of toxicity is still going strong (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%